PENGEMBANGAN MODUL PRAKTIKUM UNTUK PERBANDINGAN UNJUK KERJA LINE CODING RZ DAN NRZ PADA JARINGAN FIBER OPTIK - Aldha Rasjman Sayoga, I Putu; Sudiarta, Pande Ketut; Putra Sastra, Nyoman (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
The important thing to consider in the process of sending optical fiber network signals is the selection of line coding types. Line coding is a process of converting digital data into digital signals so that they can be transmitted in optical fiber networks. Line codings commonly used are NRZ and RZ. Therefore, this research discussed the comparison of the performance of NRZ and RZ line codings in fiber-optic networks in terms of Q-Factor, BER, and Eye Diagram. The result of this research was the characteristic form of the electric signal line coding NRZ with one data element using one signal element, while in the RZ coding line, one data element used two signal elements. The maximum rise time variable using the RZ coding line is 0.3 bits, while the NRZ coding line is 0.7 bits. The best rectangle shape model using line coding RZ is sine while line coding NRZ is exponential. The maximum bit rate using the RZ coding line is 11.5 Gbps while using the NRZ coding line is 18 Gbps. The maximum transmission distance using the RZ and NRZ coding line is 75 km. Another output of this research is a practicum module that can be used by students of the Electrical Engineering Study Program to understand optical communication systems, especially line coding RZ and NRZ. Based on the results of student assessments of 87.6% and the post-test score which is higher than the pre-test score, the practicum module is feasible as teaching material.